Visual performance after the implantation of a new trifocal intraocular lens - Vryghem JC (Dove Medical Press, 2013)
Jérôme C Vryghem,1,2 Steven Heireman1,21Brussels Eye Doctors, Brussels, Belgium; 2Clinique Saint-Jean, Brussels, BelgiumPurpose: To evaluate the subjective and objective visual results after the implantation of a new trifocal diffractive intraocular lens.Methods: A new trifocal diffractive intraocular lens was designed combining two superimposed diffractive profiles: one with +1.75 diopters (D) addition for intermediate vision and the other with +3.50 D addition for near vision. Fifty eyes of 25 patients that were operated on by one surgeon are included in this study. The uncorrected and best distance-corrected monocular and binocular, near, intermediate, and distance visual acuities, contrast sensitivity, and defocus curves were measured 6 months postoperatively. In addition to the standard clinical follow-up, a questionnaire evaluating individual satisfaction and quality of life was submitted to the patients.Results: The mean age of patients at the time of surgery was 70 ± 10 years. The mean uncorrected and corrected monocular distance visual acuity (VA) were LogMAR 0.06 ± 0.10 and LogMAR 0.00 ± 0.08, respectively. The outcomes for the binocular uncorrected distance visual acuity were almost the same (LogMAR −0.04 ± 0.09). LogMAR −010 ± 0.15 and 0.02 ± 0.06 were measured for the binocular uncorrected intermediate and near VA, respectively. The distance-corrected visual acuity was maintained in mesopic conditions. The contrast sensitivity was similar to that obtained after implantation of a bifocal intraocular lens and did not decrease in mesopic conditions. The binocular defocus curve confirms good VA even in the intermediate distance range, with a moderate decrease of less than LogMAR 0.2 at −1.5 D, with respect to the best distance VA at 0 D defocus. Patient satisfaction was high. No discrepancy between the objective and subjective outcomes was evidenced.Conclusion: The introduction of a third focus in diffractive multifocal intraocular lenses improves the intermediate vision with minimal visual discomfort for the patient.Keywords: lens implantation, trifocal diffractive intraocular lens, third focus, diffractive multifocal